2019
DOI: 10.1136/archdischild-2018-316773
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of high-flow nasal cannula therapy in preterm infants

Abstract: ObjectiveHigh-flow nasal cannula (HFNC) therapy is increasingly used in preterm infants despite a paucity of physiological studies. We aimed to investigate the effects of HFNC on respiratory physiology.Study designA prospective randomised crossover study was performed enrolling clinically stable preterm infants receiving either HFNC or nasal continuous positive airway pressure (nCPAP). Infants in three current weight groups were studied: <1000 g, 1000–1500 g and >1500 g. Infants were randomised to either first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 33 publications
2
54
0
1
Order By: Relevance
“…Several studies have already indicated overlapping actions by demonstrating that nHF can generate some distending pressure similar to CPAP. [13][14][15][16][17][18] The main differences between the two systems are that the desired pressure is set by the clinician during bubble CPAP, whereas with nHF the clinician does not set, and is not aware of, the delivered pressure. In both systems, the device set pressure and the delivered prong pressure is likely to be higher than the pressure transmitted into the airway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have already indicated overlapping actions by demonstrating that nHF can generate some distending pressure similar to CPAP. [13][14][15][16][17][18] The main differences between the two systems are that the desired pressure is set by the clinician during bubble CPAP, whereas with nHF the clinician does not set, and is not aware of, the delivered pressure. In both systems, the device set pressure and the delivered prong pressure is likely to be higher than the pressure transmitted into the airway.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The postulated mechanisms of action of nHF include reduction of dead space through the washout of nasopharyngeal carbon dioxide produced by the "high" gas flows, and the generation of a distending pressure. 5,[12][13][14][15][16][17][18] It is suggested that CPAP exerts its effects primarily through generation of distending pressure, and nHF by the high gas flow into the airway. We postulate there may be overlap between the mechanisms of action of the two modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degree of leak around the nares, mouth open or closed, degree of spontaneous breathing, and flow settings have important effects on the degree of pressure generation and therefore on support. 21,22 Liew et al 23 conducted a prospective randomized crossover study to assess the effects of HFNC on respiratory physiology. Among 44 infants whose birthweight was < 2,000 g, increasing flows from 2 to 8 L/min led to a mean increase in end-expiratory pressure of 2.3-6.1 cm H 2 O as measured with nasopharyngeal airway pressure monitoring.…”
Section: Physiologic Effects Of Hfncmentioning
confidence: 99%
“…The advantages of nHFT include ease of use, less nasal trauma, and improved patient comfort compared to nasal continuous positive airway pressure (nCPAP) 3,4 . Physiological effects of nHFT include improved alveolar ventilation by reducing dead space ventilation, generation of end‐expiratory airway pressure, improved oxygenation, lowering respiratory rate, 5 reduction in patient work of breathing 6 . Evidence from two recent systematic reviews has concluded that nHFT has shown “non‐inferiority” 7 or “similar rates” 8 for success compared to nCPAP in preterm infants greater than 28 weeks gestation postextubation.…”
Section: Introductionmentioning
confidence: 99%